Experiencias de discriminación laboral hacia jóvenes profesionales con cabello afro-rizado en Lima, Perú - Guevara Villamar, Fiorella (2022)
Racism is a current problem that generates structures of violence and structural inequality; it directly affects the individual experiences and quality of life of afro-descendant individuals. One of the ways in which this system expressed itself is in labor discrimination. Within the workplace, aesthetic categories such as “good presence” are often used to justify discrimination against individuals who, supposedly, do not fit into a professional climate. This article’s objective is to reflect on the experiences of labor discrimination against young Afro-Peruvian professionals because of their afro-curly hair in Metropolitan Lima. From the dialogue with the interviewees, it was found that the rejection of people with afro-curly hair in work spaces occurs implicitly and explicitly. This is based on stereotypes and prejudiced attitudes, and results in discrimination, which ends up reproducing and reinforcing racist structures. Faced with these, young people generate strategies that consist in the modification of their bodies, which bring consequences for the construction of their identity.